2016
DOI: 10.1126/science.aaf1204
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal subtypes and diversity revealed by single-nucleus RNA sequencing of the human brain

Abstract: The human brain has enormously complex cellular diversity and connectivities fundamental to our neural functions, yet difficulties in interrogating individual neurons has impeded understanding of the underlying transcriptional landscape. We developed a scalable approach to sequence and quantify RNA molecules in isolated neuronal nuclei from post-mortem brain, generating 3,227 sets of single neuron data from six distinct regions of the cerebral cortex. Using an iterative clustering and classification approach, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
902
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 887 publications
(981 citation statements)
references
References 37 publications
37
902
1
Order By: Relevance
“…New cell types have been found in the brain [3][4][5][6][7] , gut 8 , retina 9 and immune system 10 , and these discoveries have yielded new insight -into how the immune system 11 functions, for example, and into the dynamics of tumour ecosystems 12 . Yet, to take the next step -to build a human cell atlas that is truly useful -requires taking the long view and addressing various systemic and organizational challenges, as well as technical and scientific ones.…”
Section: Technology Revolutionmentioning
confidence: 99%
“…New cell types have been found in the brain [3][4][5][6][7] , gut 8 , retina 9 and immune system 10 , and these discoveries have yielded new insight -into how the immune system 11 functions, for example, and into the dynamics of tumour ecosystems 12 . Yet, to take the next step -to build a human cell atlas that is truly useful -requires taking the long view and addressing various systemic and organizational challenges, as well as technical and scientific ones.…”
Section: Technology Revolutionmentioning
confidence: 99%
“…However, other more complex organs such as the brain do not exhibit a corresponding number of 15 expressed genes despite the fact that they consist of a substantially greater number of distinct cell types 3,10, [14][15][16] . Moreover, recent animal studies have shown that many testis-enriched and evolutionarily-conserved genes are not required for male fertility in mice 17 .…”
Section: Main Textmentioning
confidence: 99%
“…The analyses conducted across as many as 170 brain regions and subregions (Hawrylycz et al 2012), 16 neuronal subtypes (Lake et al 2016), and 466 individual cells (Darmanis et al 2015) revealed the complex transcriptional landscape. Hence, integrated analyses of multiple brain regions in the context of human evolution may uncover alterations in spatial profiles of expression levels, revealing changes that collectively contribute to human brain functionality.…”
mentioning
confidence: 99%